A STRANGER IN THE HEART : ... brief considerations about some psychological aspects in transplantation - Sá, Eduardo (Brazilian Journal of Transplantation, 2013)
There is a line that unites a surgeon and a psychoanalyst: the immense complexity that is present in the challenge of intervening and the demand for rigorous consideration and a precise technical rigor (which does not cease to exist when we "touch" people's thoughts and bodies). But there is a point that separates them: no matter how many transplants it is feasible to perform on a person, our intervention with their thinking will be less invasive, less radical and more conservative.